2008
DOI: 10.1007/s10661-008-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

How effective has the Clean Water Act been at reducing pollutant mass emissions to the Southern California Bight over the past 35 years?

Abstract: The Clean Water Act (CWA) has regulated discharges of contaminants since 1972. However, evaluations of the CWA's effectiveness at improving regional water quality are lacking, primarily because integration of monitoring data from multiple dischargers to assess cumulative effects is not required. A rare opportunity exists to assess CWA effectiveness by integrating mass emissions data from all major sources of contaminants to the Southern California Bight from 1971 to 2000. While the coastal population grew by 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 8 publications
(10 reference statements)
2
34
1
Order By: Relevance
“…However, effluent PPCP concentrations were below currently available thresholds of chronic toxicity effects [25]. In 2000, the combined emissions of large POTWs to the Southern California Bight were 4,221 kg for polycyclic aromatic hydrocarbons and 740 kg for chlorinated phenols [27]. For example, among the 32 PPCPs detected in the present study, chronic toxicity thresholds are reported for nine of them [25].…”
Section: Discussioncontrasting
confidence: 52%
“…However, effluent PPCP concentrations were below currently available thresholds of chronic toxicity effects [25]. In 2000, the combined emissions of large POTWs to the Southern California Bight were 4,221 kg for polycyclic aromatic hydrocarbons and 740 kg for chlorinated phenols [27]. For example, among the 32 PPCPs detected in the present study, chronic toxicity thresholds are reported for nine of them [25].…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, declines on the shelf were much greater than reported for offshore stations even along similar isopycnals. Based on declines reported in other studies (Bograd et al 2008;McClatchie et al 2010), decadal variability in source water oxygen content contributes , 29% of the total observed declines in DO on the shelf between 1998-2012. In 1998 the warm phase of the PDO (1973PDO ( -1998 was replaced by cold phase (1998-present), although how the transition from warm to cold PDO resulted in the start of DO decline is presently unclear.…”
Section: Discussionmentioning
confidence: 82%
“…The coastal waters of the Southern California Bight border one of the most densely populated regions in North America and are increasingly affected by pollution from both publicly owned treatment works (POTWs) and stormwater runoff due to increasing population growth and urbanization (McKinney, 2002;Bay et al, 2003;Creel, 2003;Schiff and Bay, 2003;Crossett et al, 2004;Lyon and Stein, 2009;Gierach et al, 2017;Holt et al, 2017). The Hyperion Treatment Plant (HTP) is the largest POTW in the Southern California Bight, discharging wastewater directly into Santa Monica Bay.…”
Section: Introductionmentioning
confidence: 99%
“…The Hyperion Treatment Plant (HTP) is the largest POTW in the Southern California Bight, discharging wastewater directly into Santa Monica Bay. Servicing the Los Angeles Metropolitan Area, HTP releases a daily average of 8.71×10 5 m 3 of secondary treated effluent into Santa Monica Bay via a 5-mile (8.1 km) outfall pipe (Southern California Coastal Water Research Project, 1973;Steinberger and Stein, 2004;Lyon and Stein, 2009). However, during diversion events, when their main 5-mile outfall pipe is temporarily shut down, HTP diverts the wastewater to their 1-mile (1.2 km) outfall pipe, discharging the wastewater into the nearshore environment of Santa Monica Bay (Figure 1).…”
Section: Introductionmentioning
confidence: 99%